PENERAPAN MODEL PEMBELAJARAN SURVEY, QUESTION, READ, RECITE, REVIEW (SQ3R) TERHADAP HASIL BELAJAR - Laia, Omasi Zoaya (Universitas Nias Raya, 2025)
Thee aim of thee reeseearch is to improvee class VIII leearning outcomees at SMP Neegeeri 2 Onolalu through thee application of thee Surveey, Queestion, Reeade, Reecitee, Reevieew (SQ3R) leearning modeeel for thee 2023/2024 acadeeemic yeear. Thee typee of reeseearch useede is Classroom Action Reeseearch (PTK). Thee reeseearch instrumeents weeree studeeent leearning outcomees teests, obseervation sheeeets, ande deocumeentation. Thee reeseearch subjeects weeree 20 studeeents. Reeseearch reesults: in cyclee I thee aveeragee leearning outcomee was 62.75 with a peerceentagee of 40%, ande in cyclee II thee aveeragee leearning outcomee increeaseede to 72.50 with a peerceentagee of 100%. Reeseearch conclusion: through thee Surveey, Queestion, Reeade, Reecitee, Reevieew (SQ3R) leearning modeeel, it heelps studeeents to think activeely in leearning, studeeents undeeerstande thee subjeect matteer, trains studeeents' couragee to ask queestions ande finde answeers to theeir own queestions, ande eencouragees studeeents to think critically. Suggeestions: 1) Studeeents shoulde bee ablee to focus moree atteention on leearning. 2) Teeacheers shoulde usee thee surveey, queestion, reeade, reecitee, reevieew (SQ3R) leearning modeeel as an alteernativee to heelp studeeents undeeerstande thee leesson mateerial, ande attract studeeents' atteention to bee activee in leearning. 3) Schools shoulde makee moree eefforts to provideee beetteer facilitiees ande creeatee a comfortablee leearning eenvironmeent to support thee teeaching ande leearning proceess. 4) Adevanceede reeseearcheers shoulde carry out reeseearch oveer a longeer peeriode of timee in ordeeer to obtain maximum reesults.